PENGARUH APLIKASI RHIZOBIUM INDIGEN TERHADAP PERTUMBUHAN KEDELAI PADA ENTISOL DAN INCEPTISOL - Intan Agistia; Ricky Indri Hapsari (BUANA SAINS, 2006)
The objective of this experiment was to isolate Rhizobium bacteria from soybean and to study the effect of inoculation of the isolated indigenous bacteria on soybean growth. Six treatments comprising TA (Entisol control), TaI1 (Entisol+Rhizoplus), TaI2 (Entisol +Rhizobium indigenous), KB (Inceptisol control), TbI1 (Inceptisol+Rhizoplus), TbI2 (Inceptisol+ indigenous Rhizobium) were arranged in a completely randomized design with three replicates. Results of this study indicated that; (1) morphology of Rhizobium was shape of colony, around white, and phlegm, total colony of Rhizobium indigenous are 130 x 107 cuff/ml (2) indigenous Rhizobium had higher influence than Rhizoplus to the total of the root-nodule, the weight of dry nodule, the high of the plant, and pH, the N-total of soil, and the N-total of plant are good at an Entisol and an Inceptisol